Survey of the Anopheles mosquito alleged potentially as vectors of malaria in Aceh Besar district - Yulidar Yulidar (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2017)
Malaria is an infectious disease caused by the Plasmodium through the bite of Anopheles sp.  After the tsunami in 2004, Aceh Besar and Banda Aceh suffered various environmental changes. Environmental is one of supporting factors for high number of malaria incidences. Indicators of the increasing incidence of malaria is the increase in the value of AMI (Annual Malaria Incidence). In 2004, the value of AMI in Aceh Besar district reached 11.74 0/00 and increased to 26.34 0/00 in 2015. Vector control is one of  malaria control programs. To support the program , it had been conducted a survey of Anopheles (by collecting larvae) as the potential vector. This was was a descriptive study which was conducted in 16 sampling points in Aceh Besar district, from February to October 2007. The results showed  mean value of vector breeding pH was 7.8. The aquatic vegetation in larval breeding habitat were Spirogyra sp, Limnocharis flava, Ipomoea aquatica, Ipomoea pes-caprae), and Oriza sativa. Species of Anopheles sp found were Anopheles sundaicus, Anopheles vagus, Anopheles barbirostris, Anopheles  kochi, Anopheles maculatus, and Anopheles tesselatus.